Key performance indicators and the balanced scorecard at the Luxury Brand Hotels of Pestana Group - Marques, Beatriz Gomes (2017)
Traditional approaches to evaluate performance in hotels, have mainly used financial measures. Building on Speckbacher et al. (2003), this Work Project aims to design and propose a Balanced Scorecard Type II as a performance measurement/management system for the hospitality industry based on data collected at the Luxury Brand Hotels of Pestana Group. The main contribution is to better align the vision, strategy and financial and non-financial performance measures in this category of hotels, in particular those of Pestana Group, and by doing so, lead their managers to focus on what is really critical and, consequently improve the overall performance.